Serial Bomb Blasts in North-East India: A Postmortem Study - Malik, Yogender; Ritu Raj Chaliha , Ritu Raj (Journal of Indian Academy of Forensic Medicine, 2012)
Terrorism has become a global phenomenon and most of the countries, whether developed or  developing, are facing terror activities. Recently the terror activities have become a regular feature in  India where more than 15 major terrorist strikes occurred from 2008 to 2010. Assam, the gateway of  northeast India, on 30th October 2008 witnessed a strategically planned terrorist multiple consequential  serial bomb blast attack where more than 13 bombs were exploded within a span of merely 10-20  minutes. The news on the next day indicated the initial death of 66 persons; and 470 sustained minor to  severe injuries during the explosions in different places. Out of these ultimately 90 persons had died, which was the highest mortality in any blast in the Assam till that date. The dead bodies of 56 victims  were brought to Gauhati Medical College and Hospital mortuary for postmortem examination. During  autopsy apart from the demographic data collected on interaction with police, relatives of the victims and  inquest papers of every victim, the postmortem findings were recorded in details and the difficulties faced  in the management of this disaster in mortuary will be discussed in this paper.
Keywords: Bomb Blast; Injuries; Terrorist; Post-mortem